Clinical value and cost analysis of the sFlt-1/PlGF ratio in addition to the spot urine protein/creatinine ratio in women with suspected pre-eclampsia: PREPARE cohort study - M. Wind; M. E. van den Akker-van Marle; B. E. P. B. Ballieux; C. M. Cobbaert; T. J. Rabelink; J. M. M. van Lith; Y. K. O. Teng; M. Sueters (BMC, 2022)
Abstract Background This study investigated the clinical value of adding the sFlt-1/PlGF ratio to the spot urine protein/creatinine ratio (PCr) in women with suspected pre-eclampsia. Methods This was a prospective cohort study performed in a tertiary referral centre. Based on the combination of PCr (< 30) and sFlt-1/PlGF (≤38) results, four groups were described: a double negative result, group A−/−; a negative PCr and positive sFlt-1/PlGF, group B−/+; a positive PCr and negative sFlt-1/PlGF, group C+/−; and a double positive result, group D+/+. The primary outcome was the proportion of false negatives of the combined tests in comparison with PCr alone in the first week after baseline. Secondary, a cost analysis comparing the costs and savings of adding the sFlt-1/PlGF ratio was performed for different follow-up scenarios. Results A total of 199 women were included. Pre-eclampsia in the first week was observed in 2 women (2%) in group A−/−, 12 (26%) in group B−/+, 4 (27%) in group C+/−, and 12 (92%) in group D+/+. The proportion of false negatives of 8.2% [95% CI 4.9-13.3] with the PCr alone was significantly reduced to 1.6% [0.4-5.7] by adding a negative sFlt-1/PlGF ratio. Furthermore, the addition of the sFlt-1/PlGF ratio to the spot urine PCr, with telemonitoring of women at risk, could result in a reduction of 41% admissions and 36% outpatient visits, leading to a cost reduction of €46,- per patient. Conclusions Implementation of the sFlt-1/PlGF ratio in addition to the spot urine PCr, may lead to improved selection of women at low risk and a reduction of hospital care for women with suspected pre-eclampsia. Trial registration Netherlands Trial Register (NL8308).